Oceanic events and biotic effects of the Cenomanian-Turonian anoxic event, Tarfaya Basin, Morocco - Keller, Gerta; Adatte, Thierry; Berner, Zsolt; Chellai, E.H.; Stueben, Doris (My University, 2008)
Profound biotic changes accompanied the late Cenomanian δ13C excursion and OAE2 in planktic foraminifera in the Tarfaya Basin of Morocco. Planktic foraminifera experienced a severe turnover, though no mass extinction, beginning with the rapid δ13C excursion and accelerating with the influx of oxic bottom waters during the first peak and trough of the excursion. Species extinctions equaled the number of evolving species, though only the disaster opportunists Guembelitria and Hedbergella thrived along with a low oxygen tolerant benthic assemblage. The succeeding δ13C plateau and organic-rich black shale deposition marks the anoxic event and maximum biotic stress accompanied by a prolonged drop in diversity to just two species, the dominant (80–90%) low oxygen tolerant Heterohelix moremani and surface dweller Hedbergella planispira. After the anoxic event other species returned, but remained rare and sporadically present well into the lower Turonian, whereas Heterohelix moremani remained the single dominant species. The OAE2 biotic turnover suggests that the stress to calcareous plankton was related to changes in the watermass stratification, intensity of upwelling, nutrient flux and oxic levels in the water column driven by changes in climate and oceanic circulation. Results presented here demonstrate a 4-stage pattern of biotic response to the onset, duration, and recovery of OAE2 that is observed widely across the Tethys and its bordering epicontinental seas.
Keywords: Cenomanian-Turonian; Biotic effects; Oceanic events; Tarfaya; Morocco